Analysis of Conventional Ultrasound and Contrast-Enhanced Ultrasound Features of Pseudoangiomatous Stromal Hyperplasia - Hui Li; Qinghua Niu; Chao Jia; Gaoxiang Fan; Long Liu; Gang Li; Penglin Zou; Rong Wu; Lianfang Du; Jing Wang; Qiusheng Shi (The Breast Journal, 2025)
Conclusion: This study suggests that linear/cystic hypoechoic areas on sonography may serve as crucial clues for the ultrasound diagnosis of PASH. The presence of diffuse patchy perfusion defects in CEUS contributes to the accurate diagnosis of PASH.